Paleogeographic reconstruction of an ancient source-to-sink system in a lacustrine basin from the Paleogene Shahejie formation in the Miaoxibei area (Bohai Bay basin, east China) - Feng, Bin; He, Youbin; Li, Hua; Li, Tao; Du, Xiaofeng; Huang, Xiaobo; Zhou, Xiaoguang (Frontiers in Earth Science, 2023)
The paleogeographic reconstruction of ancient source-to-sink systems is a current focus and challenge in the field of Earth sciences; however, there are few established method or representative reconstruction case for ancient source-to-sink system paleogeographic reconstruction. Using drilling, thin-section, core, and 3D seismic data guided by sequence stratigraphy and sedimentology and the source-to-sink system approach, the source-to-sink system characteristics of the second member of the Paleogene Shahejie Formation in the Miaoxibei area of the Bohai Bay Basin were reconstructed. In addition, a new method for paleogeographic reconstruction of the ancient source-to-sink system was established using geomorphology and sediment backfilling technology to identify the erosion evolution history of the provenance area and to reconstruct the study area source-to-sink system for the investigated time-span. This study shows that a complete near-transport source-to-sink system developed in the Miaoxibei area, with the source area composed of Mesozoic granites, Neoproterozoic quartzites, and conglomerates. The primary and secondary watersheds were trending in N–S and E–W directions, respectively. The paleo drainage system trended in a N–S and E–W direction. The sedimentary facies represent mainly fan deltas and lakes. During the Paleogene, erosion was stronger in the western part of the source area than that in the eastern part, and the position of the paleo watershed gradually shifted eastward. The reconstruction method presented here and its results on the source-to-sink system can facilitate ancient source-to-sink system research in continental basins and serve as a model for paleogeographic reconstruction of ancient source-to-sink systems and related hydrocarbon exploration in other regions.